Insatisfação com a imagem corporal de meninas de 11 a 14 anos de idade - Paula Bortoluzzi De Carli; Pedro Pugliesi Abdalla; Dalmo Roberto Lopes Machado; Gustavo André Borges (Universidade Estadual do Oeste do Paraná, 2016)
The study analyzed the body image satisfaction of girls from different age groups of a private school of Marechal Candido Rondon - Pr. The sample consisted of 82 girls, aged between 11 and 14 years. Anthropometric measurements of body mass and height were obtained for the determination of body mass index (BMI). The Kakeshita body scale was used to evaluate body image satisfaction. Comparisons of the proportions of BMI classifications, satisfaction with body image and the desire to increase or reduce body scale were performed between the age groups, with the binomial test. The same variables had their proportions compared between the age groups with the chi-square test (χ2). All analyzes were performed with a previously established level of significance (α = 0.05). The results showed that 63.8% of the girls studied had BMI within the expected range and only 36.2% presented with overweight (p = 0.001) and obesity (p<0.001). However, 81.7% (p<0.001) of the girls were dissatisfied with their bodies, and 91% (p<0.05) wished to be with leaner bodies. Based on the results, most of the girls showed dissatisfaction with their body image.